Upaya Meningkatkan Kemampuan Kognitif Dalam Kegiatan Mengenal Lambang Bilangan Melalui Penerapan Metode Demonstrasi Berbantuan Media Gambar - Tri Andayani; Maharani Maharani; Amin Yusi (Jurnal Pendidikan Tuntas, 2023)
This background of this research is the low ability of children to recognize number symbols, one of the alternatives offered by researchers is the introduction of number symbols by applying the demonstration method. The research method used was classroom action research conducted in 2 cycles. Data collection methods used are observation, assignment and documentation. The results showed that the children's cognitive abilities in recognizing number symbols which developed very well in each indicator showed a good increase after the action was carried out in cycle II, where children could recognize number symbols 1-10 with a percentage of 71.4%, children could show number symbols 1-10 in sequence with a percentage of 62.0%, children paired symbol numbers 1-20 with picture media with a percentage of 76.1%, and children could name symbols of numbers 1-10 in sequence with a percentage of 76.1%. Keywords: Cognitive Abilities, Recognize Number Symbols, Demonstration Learning Methods